To Assess the Efficacy and Safety of Tacrolimus Skin Cream, 0.03% in Moderate to Severe Vernal Keratoconjunctivitis - Arsalan Ahmed, Faiza Rasheed, Sameera Irfan (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the efficacy and safety of Tacrolimus skin cream (Ecczemus 0.03%) in the resolution of moderate to severe Vernal Keratoconjuctivitis (VKC). Material and Methods: A prospective clinical trial was conducted at the oculoplastics department of a tertiary care centre, from Sep 2013 – Oct 2014. In this, 54 consecutive cases (108 eyes) with moderate to severe VKC, between the ages of 4 – 18 (mean 7 years) years were included. There were 13 newly diagnosed cases and 41 recurrent. After discontinuing their previous medications, they were treated with Tacrolimus skin cream, 0.03% applied into the lower conjunctival fornix twice a day along with lubricants for a period of 4 – 8 months. Clinical signs and symptoms were recorded at the beginning of the treatment and at all follow-ups which were conducted weekly for one month and then every month for one year. Results: The duration of therapy was 4 – 8 months (mean 6 months). The patients were followed-up for a mean duration 10 ± 1.5 months. There was marked subjective as well as objective improvement in all cases within one month of therapy. There was no need for any additional therapy. No toxic effects of Tacrolimus were observed in any case. Conclusion: It can be concluded that Tacrolimus skin cream (0.03%) is an effective therapy for moderate to severe cases of vernal keratoconjuctivitis. It acts as a safe alternative to topical steroids. Key words: Tacrolimus Vernal Keratoconjunctivitis, Allergy